PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI INTERAKSI MAKHLUK HIDUP DENGAN LINGKUNGAN KELAS VII SMP - M, Ramadhani; Suzanti, Fitra; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the level of validity of the Student Worksheet (LKPD) Based on Problem Based Learning (PBL) on the Interaction Material of Living Things with the Class VII Middle School. This research was conducted in two places, namely for the validation of the Student Worksheet (LKPD) by the validator carried out in the Biology Education Study Program at the Faculty of Teacher Training and Education, University of Riau. Then, a limited trial of LKPD that had been developed was carried out at SMPN 2 Bangko Pusako, Rokan Hilir Regency. The time of research is May-October 2019. This type of research is development research using the ADDIE model which is carried out until the development stage. There are 4 LKPD developed. Data collection instruments in this study were LKPD validation sheets, and questionnaire respondents. After LKPD is developed, it is then validated by 5 validators. After that, the first trial was conducted on 15 students of FKIP UR biology education, and the second trial on 20 Class VII students at SMPN 2 Bangko Pusako. Student Based Worksheet (LKPD) based on Problem Based Learning (PBL) on the material interaction of living things with the environment of class VII SMP has been successfully developed with a very valid category. Â Keywords: Development, Student Worksheet, Problem Based Learning